(untitled) (REVISTA NODO, 2022)
Based on the concept of coloniality, the notion of decoloniality is explained in relation to aesthetics understood as epistemological, critical, and political reflection. This relationship will allow us to elucidate the purposes of a decolonial aesthetics, which in this article will have art as the focus of analysis. It will be shown how this aesthetic approach allows art to move towards decolonial artivism, that is, towards expressive forms of meaning configuration that give rise to actions of resistance and creation against colonial systems of patriarchal and oppressive representation. After proposing that aesthetics can enrich and, at the same time, be enriched by expressions of decolonial artivism, it is shown how some works by Ana Mendieta (Cuba), Shirin Neshar (Iran) and Andrés Sierra (Colombia) invite us to think about that mutual enrichment. Finally, we refer to the exercise of collective creation called “collaborative digital cartographies” and show how this exercise enhances forms of decolonial artivism, even among those of us who are not artists.